PELATIHAN KADERISASI UNTUK PENDATAAN IBU HAMIL DENGAN CARA DIGITALISASI (GOOGLE FORM) DI DESA JATI KECAMATAN GATAK KABUPATEN SUKOHARJO - Isna Aprilia; Ayu Anisah; Novira Indah Safitri; Talitha Eka Maulinda; Iqbal Maulana Ikhsan; Milan Dwi Winanti; Ajeng Dyah Kusumaningrum; Nyimas Arsilla Restinavia; Anggitya Widyastuti; Titik Setiyowati; Kurnia Lutfi Farizqi; Beti Kristinawati; Listyani Hidayati (Universitas Muhammadiyah Surakarta, 2025)
The recording and reporting of health data carried out by cadres mostly use manual methods. The shortcomings of using manual methods in reporting include missing data, data duplication, and reporting to the health center. In addition, reporting to the health center must be in the form of a neat file, and if it continues to be done manually, it can slow down the reporting process. Advanced technology can be used as a solution to these problems, such as data collection training for cadres to create Google form where the results will be in the form of files that are neatly inputted into spreadsheet without having to work twice. The purpose of this community service is to provide training to health cadres to increase their knowledge and skills and not be stuttering about technology because today’s era is entirely digital. In addition, it also aims to facilitate cadres in the process of recording and reporting. The method used in this community service is education on creating Google form and direct training. The results of the activity show an increase in pretest and posttest scores. The conclusion of community service is that there was an increase in knowledge and skills from 3 to 10 cadres after the posttest in the data collection training using Google form. The suggestion for future activities is to work together with village officials to help provide facilities and infrastructure, such as facilitating laptops for cadres.